The Key Success Factor: A Study of Honda Motor - Alvesterlee M Muniandy; Daisy Mui Hung Kee; Saiful Izwan; Muhammad Imran; Al-Amin Al-Amin; Sumit Kumar; Shagun Singh (Journal of The Community Development in Asia, 2020)
This paper is to study how Honda Motor Company drives the organization towards success to improve their competitiveness with the best performance by its management. Honda is a production company founded by Soichiro Honda in 1946. Initially, it was known as "Honda Engineering Research" in Hamamatsu, Japan, and two years later the company changed to Honda Motor Company. Honda Motor focuses on its mission and vision that lead the advancement of mobility and provide comfort and convenience to people. Honda Motor is a leading manufacturer of motorcycles and a major producer of automobiles for the world market. Honda produces variety of model that meets customer’s preferences and satisfaction. Honda has always been very enthusiastic in innovating technology and challenging boundaries of mobility advancement. Honda Motor provides high quality service center-Honda Authorized Service Centers, where the tools, expertise and parts are tailored for every Honda. Honda promotes its products through mass media such as advertising, article, magazines, website, social media, billboards. The paper presents the key success factors of Honda and concludes with some recommendation.